Haspin kinase inhibition dampens pseudorabies virus infection in vitro - Tan, Lei; Yang, Yong; Huang, Xiaojiu; Yuan, Youqing; Wang, Kaixin; Peng, Xiaoye; He, Yiyan; Wang, Yijin; Lei, Lei; Chen, Yingyi; Duan, Deyong; Wang, Naidong; et al. (Frontiers in Veterinary Science, 2025)
Pseudorabies virus (PRV) represents a considerable infectious threat to the swine industry in China and poses potential health risks to humans. However, there is a notable lack of specific antiviral agents aimed at combating PRV. Haspin is involved in histone phosphorylation during mitosis, while the role of swine Haspin in PRV infection has not been previously investigated. In the present study, we demonstrated that Haspin expression was significantly enhanced in response to PRV infection. Overexpression of the haspin gene notably enhanced PRV infection, while genetic inhibition of haspin gene resulted in a substantial reduction in viral infection. Further investigations indicated that the Haspin kinase inhibitor CHR-6494 effectively suppressed PRV infection in a concentration-dependent manner, primarily by inhibiting viral virus replication rather than interfering with the processes of binding, entry, or release. Additionally, treatment with CHR-6494 effectively restricted Herpes simplex virus type 1 infection in Vero cells. Collectively, these findings indicate that Haspin may serve as a novel therapeutic target for the management of infections caused by Alphaherpesvirinae.